A comparison of displacement and reinforcer potency for typically developing children. Issue 2 (4th September 2019) - Carter, Adam B.; Zonneveld, Kimberley L. M.
Abstract : Previous researchers found that individuals with intellectual and developmental disabilities tend to prefer edible over leisure stimuli, although leisure stimuli may still function as reinforcers. We replicated and extended previous research in a 2‐part experiment with typically developing children. In Experiment 1, we evaluated 15 children's preference for leisure and edible stimuli. Five of 15 participants preferred edible over leisure stimuli, 3 of 15 participants preferred leisure over edible stimuli, and the remaining 7 of 15 participants did not show a preference for a stimulus class. In Experiment 2, we compared the reinforcer potency of the top‐ranked stimulus from each class with 7 of the 8 participants who showed displacement of one stimulus class. Four of 7 participants allocated more responding to the task associated with the top‐ranked stimulus and 3 of 7 participants showed no differences in responding to the task regardless of the stimulus rank.